Potency of Gewang (Corypha utan Lamk.) in Linamnutu Village, Timor Tengah Selatan Regency, Nusa Tenggara Timur Province - Sancayaningsih, Retno Peni; Maharani, Mega Fitria; Santosa, S.H.M.B. (2012)
Gewang (Corypha utan Lamk.) is a palm that grows excessively in Nusa Tenggara Timur (NTT). As one of primary commodity of NTT beside lontar, gewang is being used for many kind of products. The potency of gewang for people of Linamnutu, Timor Tengah Selatan Regency, NTT lies on its availability and dispersion in nature. This research aims to learn about density, distribution, and natural reproduction of gewang to support people in Linamnutu Village. The research data was taken by field survey and remote sensing method. Six study sites were chosen based on the image character and the road access. The results showed that total density of gewang in nature was 218 trees per hectare with natural seed reproduction of 0.002%. Total average density of gewang calculated with remote sensing method in Linamnutu Village was 210 trees per hectare in 8,000 hectare area. Total number of trees in Linamnutu Village was 1,681,034 trees. The biggest area and highest total number of trees was found in very dense category, includes 5,106 hectare with total number of 1,307,172 trees. With apropriate conservation management, this high density and number of trees in Linamnutu village could provide a promising potency for bioresources. Total biomaterial potency calculated as biomass of gewang in Linamnutu Village was 4,706,895 tonnes.